CONSIDERAÇÕES SOBRE A RESOLUÇÃO CNJ n° 125/2010: uma avaliação política da política judiciária brasileira a solução dos conflitos de interesses? - Aquino, Maria da Glória Costa Gonçalves de Sousa (2016)
This thesis aims at studying the Public Politics of the Brazilian Law Power and its focal point lies in the investigation of the political avaliation of the public politics of the unjudicialization of the interest conflicts, from the determinations established by the CNJ n° 125/2010 Resolution, which defined a new agreement in the performance of the Brazilian law activity, because of the implementation of consensual mechanisms of solution of litigations like the conciliation and the mediation The matter is analyzed from the historical perspective of the mutations of the state in its several structural versions. Moreover it influenced the functioning of the state political institutions. In the same scientific-historical chain it is analyzed the political function exerted by the state organs, focusing especially the political-institutional performance of the Law Power. In this point it is scrutinized the several classic paradigms which justify the separation of the state political powers and also intend the re-dimensionship of the functions exerted by the state. It is examined the political descentralization of the state powers in order to understand how those classic theories influenced the move of expansion of the Law Power in the structure of the Contemporary State, so enabling the exercise of the precipuons functions of the judging according to the laws, which are elaborated and created by the Legislative Power, but which themselves conditioned and submitted to the constitutional supremacy. It is made a field research from the intensification of the law performance, from the enlarged participation of the Law Power in the decisory processes in the contemporary democratic societies, in order to justify how that move promoted the judicalization and effective law activity. It is investigated the historical course of the intensification process of the law activity in Brazil, so making clear the law monopoly, moreover from the process of redemocratization of the land, whose milestone was determined through the promulgation of the Constitution of the Brazilian Federal Republic of 1988. It is presented the causes of the crisis of the Brazilian law function, emphasized by the broad processual congestion passed from the enlarged access to justice; and also the consequences fighted by the Law Power because of the problem of the excessive processual litigation and the frequent slowness of the law services, which are reflected in the determination and results obtained in the Court Reports in their numbers presented by the Law National Council. Avaliation of the originary precedents, of the formulation and the fundamentals of the public politics ofadequated treatment of interest conflicts, like a way of overcoming the mechanism of the adjudicated solution of the conflicts and aspiration to the reduction of the traditional processual demand, so enabling gradually the unjudicialization of the conflict. Equally, it is avaliated the framework of politics and the determination of their actors, included the receivers of the politics, the institutional subjects, and get the other involved in the process. It is analyzed the structure of the Permanent Uncleuses of Consensual Methods of Conflict Solution and also Citizenship, as well as its compositions, selection criteria, ways of implantation, goals and established directives by politics. Finally, it is developed an analysis on the politics perspectives, considering then the need of the redimension of the performance of the Law Power, having as basis the statistical indicators, those one more recent published by the National Council of Justice. This one enables the building of a new politics, motivated by its continuing construction and by its permanent reavaliation, so in order to make possible to get a more democratic process and involved by a precise law order, which can get a way more and more enlarged by law; and also can find pointed in an agile procedure, quick and, above all, prone to reduct the law demand, including the satisfaction of the involved ones and the modification of the social reality.